The Influence of EMU Driver Education and Training on Train Driver Competency Indonesian High Speed Rail “Whoosh” - Handoko, Handoko; Atik Siti Kuswati; Nanda Ahda Imron; prasetiyo, Alfian yuda (Politeknik Perkeretaapian Indonesia Madiun, 2024)
The Jakarta Bandung High Speed Train is a mass transportation that is a long-term permanent solution that is expected to overcome road traffic congestion on urban roads and roads to Bandung, two areas that are projected in the future to become megapolitan areas, roads in the surrounding area, reduce carbon emissions and air pollution, as well as effective steps to shift private vehicle users to mass transportation effectively (Ministry of Transportation, 2022). In order to increase the competence of the crew of fast train railway facilities, PT Kereta Cepat Indonesia China (PT.KCIC) in collaboration with the Indonesian Railway Polytechnic in Madiun organized EMU Driver education and training. The following is the number of EMU Driver education and training participants who do not yet have a certificate of competence for the crew of fast train railway facilities. While the questionnaire results on the Railway Suggestion crew competency variable are also dominated by answers agreeing or with an average of 82.99%. With these results it can be interpreted that after attending EMU Driver education and training affects the Competence of the Railway Facilities Crew where the results of the regression analysis obtained Y21.323 + 0.412. The intercept value is 21,323 which means that without the X variable, the competence of the crew of the railway facilities remains the value, namely 21,323. The t test data has a t count of 5.821 while the t table at the 5% level for 32 respondents is 2.014. Because t count t table then Ho is rejected and Ha is accepted. with a significance value of 0.000 (0.0000.05) This can be interpreted that EMU Driver education and training has a positive and significant effect on the competence of the crew of railway facilities.